University training transformation to distance learning format during covid 19 pandemic - Sergeyeva, Tetyana Viktorivna; Muzalevska, Yanina Anatoliivna; Ihnatieva, Nataliia Viktorivna (Perfect Publishing, 2021)
The article presents a systematic analysis of responses to the challenges posed by the need to move to distance learning during the COVID-19 quarantine. It presents the case of efficient transition in Ukrainian university by the general education department of foreign languages. Step-by-step strategy of transition according to stages of preparation, rules coordination, work with HR, technological maintenance, planning educational process, content creation and quality assurance is presented. The new challenges and tasks of development have been formulated.
Keywords: distance learning; e-learning, blended learning; quarantine; COVID-19; training course transition; step-by-step strategy